PUSPA HREDAYA: STILISTIKA DALAM KEKAWIN SMARADAHANA - Ni Made Ari Dwijayanthi; Ketut Suara Antara (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Kekawinas a literary works contain a deep variety of poetic value in every word and sentence. Anauthorchoosesdiction with full of aesthetic and poetic calculations to create a stylistic that makes the reader drift away in his verses. Kekawin Smaradahana by Mpu Dharmaja is an Old Javanese literary work that indulges readers with interpretations of stylistics. The consciousness of worshiping Shiva is represented by the romance of Smara-Ratih which gives birth to puspa hredaya, the highest form of consciousness. This research reveals the existence of stylistics in Kekawin Smaradahana, using Pierce's semiotic theory. The signs of poetic language will be presented through the interpretation of the Puspa Hredaya structure.Keywords:puspa hredaya, stylistic, kekawin smaradahana.